Urbanization, coal consumption and CO2 emissions nexus in China using bootstrap Fourier Granger causality test in quantiles - Cheng, Kai; Hsueh, Hsin-Pei; Ranjbar, Omid; Wang, Mei-Chih; Chang, Tsangyao (Letters in spatial and resource sciences, 2021)
This short note aims at revisiting the causal links among urbanization, coal consumption and CO 2 emissions in China using a newly developed Bootstrap Fourier Granger Causality in Quantile test over the period of 1969–2019. The quantile causality approach evaluates causal relationships in a more detailed and flexible way than the conditional mean causality analysis. While the causality definition of Granger (Econometrica 37:424–438, 1969) cannot provide information about a tail causal relation or nonlinear causalities, the Causality in Quantiles test allows us to determine whether extremely low or high changes matter for the urbanization-coal consumption- CO2 emission nexus. Granger causality test based on our proposed model indicates one-way Granger causality running from urbanization to both CO2 emissions (within 0.2 quantile) and coal consumption (within 0.4, 0.6 and 0.8 quantiles) in China. These empirical results have important policy implications for the government conducting urbanization and energy policies in China.